Association between health‐related quality of life and symptoms in patients with chronic constipation: an integrated analysis of three phase 3 trials of prucalopride. Issue 3 (11th January 2015) - Tack, J.; Camilleri, M.; Dubois, D.; Vandeplassche, L.; Joseph, A.; Kerstens, R.
Abstract Background Prucalopride is a high‐affinity 5‐HT4 receptor agonist for the treatment of chronic constipation. The aims of this study were to investigate the relationship between health‐related quality of life (HRQoL) and symptoms of constipation, and to assess the response of HRQoL to treatment using integrated data from three phase III trials of prucalopride. Methods This was an integrated analysis of data from three pivotal multicenter, double‐blind, randomized, placebo‐controlled, parallel‐group trials (ClinicalTrials.gov Identifiers: NCT00488137, NCT00483886 and NCT00485940). Relationships were investigated between Patient Assessment of Constipation Quality of Life (PAC‐QOL) scores, Patient Assessment of Constipation Symptoms (PAC‐SYM) scores, bowel movement frequency (assessed using daily diaries), and treatment. Key Results Patients treated with prucalopride 2 mg (n = 659) and placebo (n = 661) were included in the analysis. An improvement in PAC‐SYM scores correlated well with an improvement in PAC‐QOL overall score (r = 0.711) and satisfaction subscale score (r = 0.589). After 12 weeks, PAC‐QOL overall score and satisfaction subscale score significantly (p < 0.001) improved by ≥1 point (clinically relevant) in 36.5% and 44.1% of patients treated with prucalopride, compared with 18.5% and 22.4% with placebo respectively. Moreover, 39.0% of patients with an improvement in satisfaction of ≥1 point achieved ≥3 spontaneous complete bowel movements/week, compared with 7.4% of those with no improvement in satisfaction (<1 point). Conclusions & Inferences Improvements in PAC‐QOL overall score and satisfaction score were associated with improvements in symptoms of chronic constipation. Compared with placebo, treatment with prucalopride significantly improved HRQoL.